Late Pleistocene and Early Holocene Vertebrates and Paleoenvironments on the Southern High Plains, U.S.A. - Johnson, Eileen (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1986)
ABSTRACTOnly a few vertebrate faunas are known for the Southern High Plains from the late Pleistocene and early Holocene. This review focuses on vertebrate local faunas from two major localities on opposite sides of the region but in the same drainage system that provide proxy data for paleoenvironmental reconstructions from ca. 11,600 to 8600 yr BP. Both localities are archaeological sites within deeply stratified, radiocarbon-dated deposits. Four distinct, successive vertebrate local faunas are known for Lubbock Lake covering the period 11,100 to 8600 yr BP. Two distinct, successive vertebrate local faunas come from Blackwater Draw Locality # 1 for the period 11,600 to 10,500 yr BP. All of the local faunas are disharmonious but the extent of disharmony and diversity varies. Faunal elements from the Northern Plains and Southeast are the most notable. The late Pleistocene local faunas indicate mild winters which did not maintain freezing conditions and cool summers with a more effective moisture regime, reduced annual temperature fluctuation, and less seasonality. The beginnings of a warming trend, greater seasonality, and increased annual temperature fluctuation denote the early Holocene. The latest local fauna marks the last of the pluvial-related ones and heralds the end of pluvial conditions beginning around 8500 yr BP. The successive local faunas illustrate the complexity of disharmony occurring in unglaciated regimes during déglaciation of North America.